DIDACTIC CONDITIONS AND MODEL FOR CREATING ASSIGNMENTS SIMILAR TO PISA INTERNATIONAL ASSESSMENT PROGRAM ASSIGNMENTS (Conferencea, 2023)
This article focuses on the development of students' natural science literacy based on PISA assignments. Samples from PISA assignments are provided.